The Response of Salinity Stress-Induced A. tricolor to Growth, Anatomy, Physiology, Non-Enzymatic and Enzymatic Antioxidants - Sarker, Umakanta; Oba, Shinya (Frontiers in Plant Science, 2020)
The investigation was carried out to elucidate growth, anatomical, physiological, and major ROS detoxification pathway involved in tolerance of A. tricolor under salinity stress. Both VA14 and VA3 varieties exhibited the reduction in RWC, photosynthetic pigments, growth, and increased electrolyte leakage (EL), leaf anatomy adaptation under salinity stress whereas, VA14 was well adapted and performed better compared to VA3. Higher ROS accumulation was demonstrated in the sensitive variety (VA3) in comparison to the tolerant variety (VA14). Salinity stress changed the cellular antioxidant pool by increasing total carotenoids, ascorbate, proline, total polyphenol content (TPC), total flavonoid content (TFC), and total antioxidant capacity (TAC) in both varieties. Although higher increment was demonstrated in the tolerant variety, however, proline increment was much pronounced in the sensitive variety. Non-enzymatic antioxidant, ascorbate, carotenoids, TPC, TFC, TAC, and antioxidant enzyme SOD and APX were noted to be a major H2O2 detoxifier in the tolerant A. tricolor variety, where there is a comparatively lower H2O2 load. It was complemented by GPOX and CAT activity at a comparatively higher H2O2 load (in the sensitive variety). SOD contributed to the dismutation of superoxide radical (SOR) both in tolerant and sensitive variety; however, it greatly contributed to the dismutation of SOR in the tolerant variety. Increase in SOD, ascorbate, and APX predominantly evident that SOD and AsA–GSH cycle had greatly contributed to quench ROS of the tolerant variety of A. tricolor.